Perception of Social Benefits - International Perspective - Jurek, Łukasz; Kozyra, Cyprian; Rojek-Nowosielska, Magdalena (Studia Oeconomica Posnaniensia, 2019)
Social benefits arouse a lot of controversy. The common belief is that the availability of those benefits has a negative impact on the basic foresight and resourcefulness, or colloquially speaking: they make people lazy. The aim of the paper is, firstly, to present the frequency of the belief that social benefits make people lazy (in selected EU countries) and, secondly, to indicate the factors determining differences in such perceptions. Data from the 8th round of the European Social Survey ware used for this purpose. An analysis of a linear correlation and multiple linear regression model were applied. The negative attitude towards social benefits was most strongly positively dependent on the rate of material deprivation, but negatively dependent on the share of the migrant population.